2000
DOI: 10.1021/ic991415s
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium(IV) and -(V) Complexes with O,N-Chelating Aminophenolate and Pyridylalkoxide Ligands

Abstract: Two different monoanionic O,N-chelating ligand systems, i.e., [OC6H2(CH2NMe2)-2-Me2-4,6]- (1) and [OCMe2([2]-Py)]- (2), have been applied in the synthesis of vanadium(V) complexes. The tertiary amine functionality in 1 caused reduction of the vanadium nucleus to the 4+ oxidation state with either [VOCl3], [V(=NR)Cl3], or [V(=NR)(NEt2)3] (R = Ph, (3a, 5a), R = p-Tol (3b, 5b)), and applying 1 as a reducing agent resulted in the synthesis of the vanadium(IV) complexes [VO(OC6H2(CH2NMe2)-2-Me2-4,6)2] (4) and [V(=N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…Recently we reported that the use of ortho-aminophenolates in vanadium(V) chemistry gave rise to the formation of vanadium(IV) compounds. [5] Consequently, the formation of a vanadium(V) chloride in the reaction of 5 with SOCl 2 would immediately result in the reduction of the vanadium(V) nucleus to yield a vanadium(IV) vanadate species and a quaternary ammonium substituent (see Scheme 5). As two amine functionalities are present in the molecule, the reaction sequence can occur twice.…”
Section: Synthesis Of Vanadium(iv) Phenolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we reported that the use of ortho-aminophenolates in vanadium(V) chemistry gave rise to the formation of vanadium(IV) compounds. [5] Consequently, the formation of a vanadium(V) chloride in the reaction of 5 with SOCl 2 would immediately result in the reduction of the vanadium(V) nucleus to yield a vanadium(IV) vanadate species and a quaternary ammonium substituent (see Scheme 5). As two amine functionalities are present in the molecule, the reaction sequence can occur twice.…”
Section: Synthesis Of Vanadium(iv) Phenolatesmentioning
confidence: 99%
“…[4] It turns out that these ligands cannot be employed in vanadium(V) chemistry, since the ortho-amino function causes reduction of the vanadium(V) center to vanadium(IV). [5] Therefore, in our further studies we have focused on employing these ortho-aminophenolate ligands in systems with the vanadium center in the formal 3 ϩ or 4 ϩ oxidation state. …”
Section: Introductionmentioning
confidence: 99%
“…[78] The imido compound {V(N-4-MeC 6 3 ] (note that ranges of activities are quoted here since many different conditions were used by these authors). In all cases very high molecular weight polymer was produced making GPC analysis difficult, and no information on the molecular weight distribution was reported.…”
Section: Other Vanadium(v) Compoundsmentioning
confidence: 99%
“…18). 36 Ligand a was used in vanadium (V) showed almost no activity under similar circumstances and for both complexes the activities were much lower than those of the non-chelated counterparts. We tentatively assign this decrease in activity to a smaller number of catalytically active species.…”
Section: Vanadium(iii)mentioning
confidence: 99%